2019
DOI: 10.1177/2382120519859300
|View full text |Cite
|
Sign up to set email alerts
|

Three-Tiered Advocacy: Using a Longitudinal Curriculum to Teach Pediatric Residents Advocacy on an Individual, Community, and Legislative Level

Abstract: Background: Pediatricians play a critical role as health advocates. Teaching residents to advocate for their patients on an individual, community, and legislative level is a priority for residency training programs. This study examined the effects of a longitudinal curriculum teaching 3-tiered advocacy on pediatric residents’ attitudes, knowledge, and practice. Methods: This was a prospective pre- and postintervention study using an anonymous survey of pediatric residents (N = 78) in an urban academic children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…95 Unfortunately, little is known how to train workers to conduct SDOH activities and which approaches are best fit for the different types of workers. The only studies that explicitly evaluated the training components of their models were with those that used pediatric residents, [35][36][37][38][39] possibly due to the growing emphasis on SDOH in post-graduate medical education. 96 Future efforts should test and optimize training materials and certification opportunities for nonphysician workers to maximize efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…95 Unfortunately, little is known how to train workers to conduct SDOH activities and which approaches are best fit for the different types of workers. The only studies that explicitly evaluated the training components of their models were with those that used pediatric residents, [35][36][37][38][39] possibly due to the growing emphasis on SDOH in post-graduate medical education. 96 Future efforts should test and optimize training materials and certification opportunities for nonphysician workers to maximize efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-eight studies were conducted with primary care patients, [29][30][31][72][73][74]76,[78][79][80][81][82][83][84][85][86][87][88][89] 4 took place in a specialty clinics, 32,71,75,77 1 took place in urgent care, 27 and 3 took place across multiple settings (eg, primary, specialty, and urgent care). 26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56][57][58]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 3 more Smart Citations